Technical and economic performance of combined harvester in farmers field (Bangladesh Journal of Agricultural Research, 2015)
Labour scarcity, harvesting loss, timely harvesting and harvesting cost are crucial in rice and wheat harvesting in Bangladesh. Combine harvester is a newly introduced harvesting machine in Bangladesh. This study was undertaken to evaluate the technical and economic performance of combine harvester available in farmers? field and farmer?s perception regarding the use of combine. Field tests of two new (CLASS andDaedong) and two refresh (Kukje and Anower) combine harvesters were conducted for harvesting rice and wheat in the farners? field of Jessore, Pabna,Dinajpurand Thakurgaon districts during 2011-12. Primary data were collected from 30 adopter and 30 non-adopter farmers from each district of Bogra, Rangpur, Dinajpur and Thakurgaon through direct interviewingduring 2012-13. Information was also collected from different combine harvester traders available in Bangladesh. Average time, cost and grain saving by combine harvester over manual methods were 97.50, 35.00 and 2.75%, respectively. Benefit cost ratio of CLASS, Daedong, Kukje and Anower combine harvesters were found to be 2.68, 2.11, 2.29 and 2.70, respectively. The payback periods of refresh combine harvesters were lower than the new combine harvester. There were some mechanical problems observed in refresh combine harvesters during field operations. New harvester was observed almost trouble free and popular to the famers. Scarcity of spare parts and mechanic service were the main problems for repair and maintenance of the combine harvesters in farm level. Considering the technical performance of combine harvester and demand of the farmers, new combine harvester may be introduced in commercial basis in Bangladesh.Bangladesh J. Agril. Res. 40(2): 291-304 June 2015